The Development of Social Work as a Speciality and the Profession in Estonia - Riina Kiik; Reeli Sirotkina (Social Work & Society, 2005)
For Estonia and its people social work is one of the vitally important fields that had to be built up from almost nothing since independence was regained in 1991. During Soviet times social work and social workers did not receive the necessary attention. Severe social problems were denied and kept hidden since according to official communist ideology, life in the Soviet Union was the best in the world and getting better all the time. Social workers did not receive specialised education and their functions were to be carried out by the workers of trade unions and the party, by teachers and by the workers of the personnel departments. In the 1990s big changes, having also an effect on social life, took place in the development of Estonian society. Concepts such as social work and social worker were rediscovered in Estonia. There are certain prerequisites for the success of any activity (including social work). One of the most important ones is being a professional, a worker with thorough preparation. Social work as an occupation requires specialised academic education, which is based on theoretical knowledge and practical skills that have been acquired through theoretical knowledge. Specialised knowledge is a foundation for attaining a specialised qualification. However, at the same time one has to keep in mind that social work as an occupation is constantly changing, there is no absolute knowledge - everything is relative, dynamic and changing (Tamm, 1998). The changing nature of the activity requires reflection by a social worker, who also has to be able to evaluate his/her work and its basis and learn from experiences. Academic specialised education implies also the development of a new professional identity and higher levels of competence. This underlines the necessity of specialised education.